Des amphores de l’oppidum de Châteaumeillant (Cher) : le matériel des fouilles des xixe et xxe s. - Fanette Laubenheimer; Céline Barthélemy-Sylvand (Gallia)
Châteaumeillant is famous for its “amphorae cellars or pits” discovered during the 19th and 20th centuries. The chronology of the findings and the analysis of existing information about these deposits lead to the detailed study of the finds kept in the Émile-Chénon museum. These finds, mostly Graeco-italic and Dressel 1 amphorae, often intact (several hundreds of them), provide precious informations concerning typology, volume and weight of these containers, such as a catalogue of stamps and tituli picti. They bring out formerly missing dating evidence, discussion on amphorae deposits and a view of the origin and trade patterns and circulation of the wine imported by this powerful Late Iron Age oppidum.